2015
DOI: 10.1111/tbed.12358
|View full text |Cite
|
Sign up to set email alerts
|

First Experimental Evidence for the Transmission ofChlamydia psittaciin Poultry through Eggshell Penetration

Abstract: Eggshell penetration by pathogens is considered a potential route for their transmission in poultry flocks. Additionally, in case of zoonotic pathogens, contact with infected eggs or their consumption can result in human infection. Chlamydia psittaci is a zoonotic bacterium that causes a respiratory disease in poultry and humans. In this study, we provide an experimental evidence for eggshell penetration by C. psittaci. Additionally, we show that after eggshell penetration, C. psittaci could eventually infect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Vertical transmission of C. psittaci was already reported in chickens and turkeys (9,31,32). In our study, only five samples from dead embryos (unhatched eggs) were found positive, whereas all cloacal swabs (n ϭ 105) obtained from 1-day-old ducklings at the hatchery were negative for chlamydiae.…”
Section: Discussionsupporting
confidence: 47%
“…Vertical transmission of C. psittaci was already reported in chickens and turkeys (9,31,32). In our study, only five samples from dead embryos (unhatched eggs) were found positive, whereas all cloacal swabs (n ϭ 105) obtained from 1-day-old ducklings at the hatchery were negative for chlamydiae.…”
Section: Discussionsupporting
confidence: 47%
“…Research on natural melanin has demonstrated that this molecule has potential pharmacological value. Melanin has been applied in cosmetics, functional foods, and other fields [ 4 ]. There has been some melanin research in multiple species, including bacteria [ 5 , 6 ], fungi [ 7 ], sponges [ 8 ], catfish [ 9 ] and black-boned sheep [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…(1) Artificial insemination procedures facilitate chlamydial dissemination from male birds to female birds and cross-infection among the female flock. C. psittaci is reported to infect other birds via vertical route [23][24][25][26] and horizonal transmission [27,28]. Moreover, Chlamydia infection might be associated with estrogen secretions during peak production.…”
Section: Multi-agents Of Salpingitis During Production Peak Of Laying Hens and Breeder Ducksmentioning
confidence: 99%